Representasi Penyimpangan Agama dalam Web Series Bidaah - Irfan, M.; Azizah, Nurul (ALAMTARA, 2025)
Web series, also known as web series, are a rapidly growing form of digital media. One phenomenal web series that has captured public attention is the Malaysian web series "Bidaah." This web series became a trending topic due to its depiction of religious deviations and achieved 2.5 billion views in a relatively short period of time, from March 6 to April 6, 2025. This study aims to uncover the symbolic meanings and hidden messages related to the religious deviation practices contained in the series. This research also used qualitative methods with an interpretive approach. The data sources were all scenes in the Bidaah web series, from episodes 1 to 13, that contain symbols of religious deviation. Data analysis employed Roland Barthes' semiotic analysis, which distinguishes between denotative, connotative, and mythical meanings. The results show that the Bidaah series depicts various deviant practices that manipulate religious symbols and legitimacy as a means of social control, reflecting authoritarian domination and oppression in the religious sphere. This study provides important insights into the complexities of religious abuse in digital media and emphasizes the need for critical awareness and strengthened religious education to prevent such abuse.